Leukotriene D4 induces cognitive impairment through enhancement of CysLT1R-mediated amyloid-β generation in mice - Tang, Su-Su; Wang, Xiao-Yun; Hong, Hao; Long, Yan; Li, Yong-Qi; Xiang, Guo-Qing; Jiang, Li-Ying; Zhang, Han-Ting; Liu, Li-Ping; Miao, Ming-Xing; Hu, Mei; Zhang, Ting-Ting; et al. (Neuropharmacology, 2013)
Amyloid plaques in the extracellular parenchyma mainly consist of amyloid-β peptides (Aβ), one of the pathological hallmarks in Alzheimer's disease (AD). In the present study, we examined neuroinflammation, amyloidogenesis, and memory performance following intracerebral infusions of leukotriene D4 (LTD4) in mice. The results demonstrated that intracerebral infusions of LTD4 (1 ng/mouse) produced memory impairment as determined by Morris water maze test and Y-maze test in mice, and caused the accumulation of Aβ1–40 and Aβ1–42 in the hippocampus and cortex through increased activity of β- and γ-secretases accompanied with increased expression of amyloid precursor protein (APP). LTD4 also induced expression of cysteinyl leukotriene receptor 1 (CysLT1R) and NF-κB p65 in the hippocampus and cortex. Pretreatment with pranlukast (1.5 ng/mouse, intracerebroventricularly), a CysLT1R antagonist, blocked LTD4-induced amyloidogenesis, memory deficits. Pranlukast (0.6 μM) also prevented LTD4 (20 nM)-induced amyloidogenesis in the cultured neurons in vitro. Moreover, LTD4-induced increases in CysLT1R and NF-κB p65 in the brain were also attenuated by pranlukast. These results suggest that LTD4 increases Aβ peptide burden via activation of CysLT1R, which further affects APP levels and activity of β- and γ-secretases via the NF-κB pathway. Our findings identify CysLT1R signaling as a novel proinflammatory and proamyloidogenic pathway, and suggest a rationale for development of therapeutics targeting the CysLT1R in neuroinflammatory diseases such as AD. ► LTD4 may induce cognitive impairment in mice. ► LTD4-induced cognitive impairment is mediated by activation of CysLT1R. ► CysLT1R-trigered NF-κB signaling promotes Aβ generation through β-secretase pathway.